Effects of four types of natural bait on water quality, feeding, growth, and antioxidant enzyme activity of Monopterus albus in a recirculating aquaculture system - Yuan, Quan; Wu, Chengcheng; Yang, Hang; Lv, Weiwei; Huang, Weiwei; Zhang, Qinghua; Zhou, Wenzong (Frontiers in Physiology, 2024)
One of the bottlenecks in M. albus aquaculture is the high mortality rate and low feeding initiation rate from stocking wild fry to the initiation of feeding. In production, trash fish is commonly used to wean M. albus juveniles onto feeding. In this study, we introduced three other natural feeds, earthworms (EW), yellow mealworms (YMW), and fly maggots (FM), with frozen trash fish (TF) serving as the control group, to evaluate the effects of these four natural feeds on the survival rate, feeding initiation, antioxidant enzymes activity, and body composition of M. albus juveniles. The experiment comprised four treatments, each with three replicates. Each replicate consisted of stocking 150 M. albus juveniles weighing 10.02 ± 0.89 g in size, raised for 5 weeks. The survival rate of the YMW group was 73.33–85.33%, which was significantly higher than that of the other three bait groups (P < 0.05). The four bait groups showed no significant differences in final body weight and specific growth rate (SGR) (P > 0.05). The EW group showed the highest final body weight, with an average SGR of 2.73, whereas the YMW group had an average SGR of 1.87. The average daily feeding amount was significantly higher in EW and YMW groups than in the other two groups (P < 0.05). The percentage of feeding amount to fish weight in the EW group reached 7.3% in the fifth week. After five weeks of cultivation, NO2--N content was significantly higher in the waters of the TF and EW groups than in the waters of the FM and YMW groups (P < 0.05), there was no significant difference in TAN content among the treatment groups (P >0.05). Liver malondialdehyde content was significantly higher in the TF group than in the other bait groups (P < 0.05).GSH-Px activity was significantly higher in the EW group than in the FM group and YMW group. The increase in crude protein content was significantly higher in the TF group than in the FM group, but the increase in crude ash content was significantly lower in the TFgroup.